PENGARUH MODEL PEMBELAJARAN ROLE PLAYING TERHADAP HASIL BELAJAR KOGNITIF MATERI OPERASI HITUNG BILANGAN CACAH - Aroyo, Elisiana; Hartoyo, Agung; Ghasya, Dyoty Auliya Vilda (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2025)
Students in elementary school are still at the stage of concrete operational thinking. Mathematics is a abstract learning abstract, Therefore, it is challenging for elementary school pupils to comprehend the study of mathematics effectively and efficiently. The purpose of this study is to characterize how the role-playing learning approach affects fourth-grade students in improving their academic abilities. This study used a quasi-experimental one-group pre-test-posttest design using experimental methodology that was carefully implemented. With a t test result of 0.000 and an effect size of 1.28, the research's findings demonstrate the significant positive impact of applying the role-playing learning model. The KKM IS 65 is cited in the success of student learning outcomes. There are 28 student who received treatment and students who got a score of 65 after being given the post-test were 11 compared to 20 students during the pre-test. Based on the results obtained, Therefore, it can be said that the roleplaying learning approach significantly improves student learning results in various aspects